Design and application of a medical protective face screen (一种医用防护面屏的设计与应用) - LI Die (李蝶); LI Feng (李凤); ZHOU Yun (周云) (Association of Integrative Nursing, 2023)
This paper introduced the design and application of a medical protective face screen. The new typeface screen is designed to reduce the risk of exposure to infection and improve the wearing comfort. This new typeface screen helps keep the outdoor medical workers from heat exhaustion. (本文介绍一种医用防护面屏的设计与应用, 在降低暴露风险的同时提升医务人员舒适感。该医用防护面屏也有助于日常室外作业人员的有效防暑降温, 降低中暑风险, 提升工作效率。)